2012
DOI: 10.1089/tmj.2011.0231
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of Remote Telemonitoring in COPD

Abstract: The addition of RM to SBP was feasible but did not reduce healthcare utilization or improve quality of life in this group of patients already receiving comprehensive respiratory care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(114 citation statements)
references
References 19 publications
3
104
0
7
Order By: Relevance
“…Most of them (4/6) reported a reduction in number of COPD-related hospitalizations, with a risk reduction ranging from 14% [18] to 69% [17]; no study, however, reached statistical significance. Only Chau et al [13] reported a non-statistically significant increase in number of COPD-related hospitalization; Pinnock et al did not document a difference between the two groups [16].…”
Section: Effect On Copd-related Hospital Admissionsmentioning
confidence: 90%
See 2 more Smart Citations
“…Most of them (4/6) reported a reduction in number of COPD-related hospitalizations, with a risk reduction ranging from 14% [18] to 69% [17]; no study, however, reached statistical significance. Only Chau et al [13] reported a non-statistically significant increase in number of COPD-related hospitalization; Pinnock et al did not document a difference between the two groups [16].…”
Section: Effect On Copd-related Hospital Admissionsmentioning
confidence: 90%
“…Five studies used the St. George's Respiratory Questionnaire (SGRQ). A statistically and clinically (>= 4 points) significant improvement in SGRQ score was reported only by Koff et al Two trials documented a non-statistically significant change >= 4 points in SGRQ in telemonitoring group compared with control group [18,21] and four studies did not show differences in quality of life between groups [11,13,14,16].…”
Section: Effect On Quality Of Lifementioning
confidence: 94%
See 1 more Smart Citation
“…Данная рекомендация основана на РКИ [118][119][120], проанализированных в систематическом обзо ре [121], и дополнительных РКИ [122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139]. Из них только 6 исследований были объединены для данной рекомендации [127,[130][131][132][133][134], хотя эксперты также принимали во внимание и результаты других иссле дований, не включенных в метаанализ.…”
Section: клинические рекомендацииunclassified
“…A randomised, controlled trial of 1,653 patients across 33 cardiology practices in the USA, suggested that there was no significant difference in hospital readmissions, length of stay, and mortality rate within 180 days after study enrolment . Another study examining hospital admission rates and hospital length of stay in patients with chronic obstructive pulmonary disease (COPD) indicated that remote monitoring did not support favourable results in hospital utilisation (Antoniades et al, 2012).…”
Section: Quality and Millmentioning
confidence: 99%